Ecotourism Governance: A Sustainable Approach for The Tongke-Tongke Mangrove Forest Destination - Suardi Muhlis; Sumardi (Journal of Transformative Governance and Social Justice, 2026)
Tongke-Tongke Mangrove Forest, located in Sinjai Regency, South Sulawesi, is an ecotourism destination that offers natural tourism and environmental education. However, it is not yet at an optimal level of management. This study aims to formulate a comprehensive Ecotourism Governance approach for the management of the Tongke-Tongke Mangrove Forest to strike a balance among conservation, local-scale economic empowerment, and tourist destination competitiveness. The research uses qualitative methods with a comparative study. Interviews, documentation, observation, and focus group discussions were used in data collection. Data analysis was conducted using coding techniques and triangulation in NVivo 12 Plus for data visualization to ensure the validity and reliability of the research findings. The study indicates that Tongke-Tongke Mangrove Forest ecotourism management is still constrained by several key factors, such as a lack of infrastructure, limited local community participation, poor coordination among stakeholders, and low levels of environmental awareness, which ultimately lead to suboptimal ecosystem conservation and tourism experiences. Moving forward, to contextualize this gap, the implementation of ecotourism governance is proposed through an integrated approach comprising infrastructure upgrading, community empowerment, stakeholder coordination strengthening, and adaptive monitoring mechanisms based on the environmental concerns from a sociocultural perspective in order to achieve mangrove conservation towards improving community welfare along with sustainable tourism destination development.